Pengembangan Media Pembelajaran Kosakata Baku Bahasa Indonesia Berbasis Game Android untuk Siswa Sekolah Dasar - An’ars M. Ghufroni; Yulia Siska; Ambyah Harjanto; Dina Maryana (LPPM STKIP PGRI Bandar Lampung, 2022)
This study aims to develop learning media based on Indonesian vocabulary game applications for elementary school students. The method in this study is Research and Development by adopting seven of the ten steps of Borg and Gall's development research. The research instrument used a Likert scale and a questionnaire. This development research uses seven steps including (1) preliminary study (potential problems), (2) data collection, (3) product design (development of initial product designs/drafts), (4) design validation by experts, (5) product revision results of initial field trials, (6) product trials (main field testing), (7) improvement of product field test results (revision of operational products). The results of testing the value of developing learning media based on vocabulary game applications fall into the feasible category.